PENGARUH KINERJA KEUANGAN TERHADAP FLUKTUASI HARGA SAHAM BANK UMUM SYARIAH DI INDONESIA - Dunakh, Fatimah Tasya Rabhita Selba; Budianto, Eka Wahyu Hestya (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study intends to investigate the influence of Earning Per Share (EPS), Price to Earning Ratio (PER), Price to Book Value (PBV), and Debt to Equity Ratio (DER) on the stock prices of Islamic Commercial Banks in Indonesia between 2019 and 2023. The research method used is quantitative with an associative approach. The research population includes 14 Islamic Commercial Banks registered with the Financial Services Authority (OJK), with a sample of 5 banks selected through a purposive sampling technique. Data were analyzed using Eviews 12 software. The results indicate that EPS has a positive and significant effect on stock prices, suggesting that an increase in earnings per share can attract investor interest. On the other hand, PER has a negative influence, indicating that investors tend to avoid stocks with valuations considered too high. PBV also has a positive impact, reflecting that a high book value can boost investor confidence. Meanwhile, DER has a positive effect, although it should be noted that a high debt-to-equity ratio can increase financial risk. Overall, these findings provide important insights for investors and bank management in making strategic decisions regarding investments and financial management. This research is expected to serve as a reference for the development of Islamic finance literature and capital markets in Indonesia.